A novel serine protease secreted by medicinal maggots enhances plasminogen activator-induced fibrinolysis - Van Der Plas, Mariena J A; Andersen, Anders S.; Nazir, Sheresma; Van Tilburg, Nico H.; Oestergaard, Peter R.; Krogfelt, Karen A.; Van Dissel, Jaap T.; Hensbergen, Paul J.; Bertina, Rogier M.; Nibbering, Peter H. (PLoS ONE, 2014)
Maggots of the blowfly Lucilia sericata are used for the treatment of chronic wounds. As haemostatic processes play an important role in wound healing, this study focused on the effects of maggot secretions on coagulation and fibrinolysis. The results showed that maggot secretions enhance plasminogen activator-induced formation of plasmin and fibrinolysis in a dose- and time-dependent manner. By contrast, coagulation was not affected by secretions. Biochemical studies indicated that a novel serine protease within secretions, designated Sericase, cleaved plasminogen to several fragments. Recombinant Sericase degraded plasminogen leading amongst others to the formation of the mini-plasminogen like fragment Val454-plasminogen. In addition, the presence of a non-proteolytic cofactor in secretions was discovered, which plays a role in the enhancement of plasminogen activator-induced fibrinolysis by Sericase. We conclude from our in vitro studies that the novel serine protease Sericase, with the aid of a non-proteolytic cofactor, enhances plasminogen activator-induced fibrinolysis.